Perception of self-medication among university students in Saudi Arabia - Mustafa S Saeed; Ali S Alkhoshaiban; Yaser Mohammed Ali Al-Worafi; Chiau Ming Long (Archives of Global Professionals, 2014)
The aim of this study is to assess self-medication practice among university students in the Al-Qassim Province of Saudi Arabia. A cross-sectional community-based survey was conducted by distributing a self-administered 18-item questionnaire among university students in the Al-Qassim Province of Saudi Arabia in the period between October and December 2012. The participants were selected using a convenience sampling technique. Data were collected from the questionnaire and analyzed using SPSS version 19. A total of 354 male students with an average age of 21.95 (SD ± 3.43) participated in this study. Our study showed that self-medication among male students was high (86.6%) compared to results shown in other studies in the same region. Headache (59.9%), cough/cold (41%) and fever (24.6%) were the most common symptoms associated with self-medication. Congruent with the medical conditions reported, the most widely used medications without prescriptions were paracetamol (34.7%), followed by antibiotics (31.4%) and nonsteroidal anti-inflammatory drugs (28.7%). Our study shows that antibiotics were sometimes irrationally used for self-treatment of cough and fever. Self-medication was highly frequent among the students. Influence of TV advertisements, high accessibility of pharmacies and convenience stores, as well as good buying power were found to be leading factors for self-medication among male university students.